Primary amine recognition in water by a calix[6]aza-cryptand incorporated in dodecylphosphocholine micelles1. Issue 10 (14th March 2015) - Brunetti, Emilio; Inthasot, Alex; Keymeulen, Flore; Reinaud, Olivia; Jabin, Ivan; Bartik, Kristin
<x xml:space="preserve">Abstract</x> A zinc calix[6]azacryptand complex was incorporated into dodecylphosphocholine micelles. This complex can strongly and selectively bind linear primary amines in an aqueous medium.